Integrasi Rencana Strategis dalam Praktik Manajerial Sekolah: Kajian Kualitatif di Lingkungan Pendidikan Menengah (Jurnal Sosial Humaniora dan Pendidikan, 2025)
In the context of secondary education, the Strategic Plan (Renstra) is an essential instrument in directing the implementation of school performance in a structured and long-term orientation. This study aims to evaluate the implementation of the Strategic Plan-based school performance implementation system in Minahasa Regency, by highlighting the integration of strategies into managerial practices, leadership effectiveness, and stakeholder participation. Using a qualitative approach of case studies, data was collected through in-depth interviews, participatory observations, document analysis, and questionnaires that were distributed to school principals, teachers, education staff, and school committees. The study results show that although most schools have prepared the Strategic Plan document according to the provisions, its implementation has not been thoroughly internalized in daily operational management. Many schools still position the Strategic Plan as an administrative document without integrating it into the evaluation and strategic decision-making process. The role of the principal as a strategic leader greatly determines the success of the implementation, but the uneven leadership capacity is a significant challenge. Stakeholdeconsider the Strategic Planr participation, especially teachers and the community, is also still minimal, while the evaluation system does not use comprehensively structured performance indicators. These findings underscore the importance of strengthening collaborative organizational culture, strategic leadership training, and the development of data-driven performance measurement systems. This research contributes to the literature on strategic education management. It opens opportunities for further exploration related to the digitalization of the Strategic Plan and the integration of strategy-based school performance evaluation.